The Far Right Culture War on ESG - Chris Crews (Religions, 2023)
This article examines connections between religious nationalism, extremist movements, and environmental politics, with a focus on environmental, social, and governance (ESG) frameworks and debates in the United States since 2020. It begins with a brief history of ESG, then examines responses from mainstream conservatives and far-right groups to the growth of ESG. It argues that the current backlash against the use of ESG is part of a larger conservative culture war against “woke” politics. The article offers a detailed look at the role of the conservative advocacy group Heritage Action and its “ESG Hurts” campaign, and shows how climate denial, conspiracy theories, and hostility to race and gender politics are interconnected parts of a growing ideological movement rooted in Christian Nationalism and climate denial.